Bisphenol-A Abrogates Proliferation and Differentiation of C2C12 Mouse Myoblasts via Downregulation of Phospho-P65 NF-κB Signaling Pathway - Chittipong Tipbunjong; Thanvarin Thitiphatphuvanon; Chumpol Pholpramool; Piyaporn Surinlert (Journal of Toxicology)
Previous studies showed that bisphenol-A (BPA), a monomer of polycarbonate plastic, is leached out and contaminated in foods and beverages. This study aimed to investigate the effects of BPA on the myogenesis of adult muscle stem cells. C2C12 myoblasts were treated with BPA in both proliferation and differentiation conditions. Cytotoxicity, cell proliferation and differentiation, antioxidant activity, apoptosis, myogenic regulatory factors (MRFs) gene expression, and mechanism of BPA on myogenesis were examined. C2C12 myoblasts exposed to 25–50 µM BPA showed abnormal morphology, expressing numerous and long cytoplasmic extensions. Cell proliferation was inhibited and was accumulated in subG1 and S phases of the cell cycle, subsequently leading to apoptosis confirmed by nuclear condensation and the expression of apoptosis markers, cleaved caspase-9 and caspase-3. In addition, the activity of antioxidant enzymes, catalase, superoxide dismutase, and glutathione peroxidase was significantly decreased. Meanwhile, BPA suppressed myoblast differentiation by decreasing the number and size of multinucleated myotubes via the modulation of MRF gene expression. Moreover, BPA significantly inhibited the phosphorylation of P65 NF-κB in both proliferation and differentiation conditions. Altogether, the results revealed the adverse effects of BPA on myogenesis leading to abnormal growth and development via the inhibition of phospho-P65 NF-κB.